Авангардні пошуки у львівському мистецтві початку ХХ століття - Biryulov, Yuri (Przegląd Wschodnioeuropejski, 2025)
The author analyzes avant-garde works created in the multinational artistic environment of Lviv at the beginning of the 20th century. At that time, the Secession (Art Nouveau), Impressionism and Post-Impressionism styles dominated in Lviv art, however, striving for a new artistic language, painters and sculptors turned to a wide range of creative expression, introduced a variety of stylistic, genre and thematic innovations. Particular attention was paid to the texture, materials, unusual composition, rich color palette, emotionally heightened images. For the first time in the study of art, the still unexplored question of the imaginative-stylistic originality of the works of these masters is comprehensively revealed. New, previously unknown works and facts are introduced into scientific circulation. It was found that the style of expressionism was most actively used, in particular, it clearly manifested itself in the works of F. Pautsch and G. Gwozdecki. Among other new trends, Lviv artists were also interested in fauvism, cubism, and abstractionism. Avant-garde experiments were accompanied by theoretical justifications from leading art critics. The research is based on the methods of art history and comparative historical analysis, principles of iconology, based on the system-structural and dialectical-philosophical approaches. A significant source base is made up of articles, reports and messages found in rare periodicals of the beginning of the 20th century.